Interaction and meaning in K-Pop interviews: A conversation analysis of NCT127 on the BUILD Talk Show - Purwanti, Eko; Astutiningsih, Rini Tri; Sari, Mariska Intan; Meisa, Wistri; Suryadi, Dedi; Dharmayanti , Margaretha (Universitas Ahmad Dahlan, 2024)
Understanding conversation analysis (CA) in a K-pop interview setting offers valuable insights into how multilingual speakers manage turn-taking, negotiate meaning, and engage in structured dialogue within a media context. This study examines the interactional patterns in an interview between Kevan Kenney and the K-pop idol group NCT127 on the BUILD talk show. Using a Conversation Analysis (CA) approach, this research aims to identify the CA aspects that emerge during the interview and to explore their communicative functions. A qualitative approach, specifically a descriptive qualitative method, was employed to analyze the primary data, which consisted of a video interview and its conversational transcript. The findings reveal the presence of key CA elements, including opening conversation, adjacency pairs, preference organization, turn-taking, feedback, repair, and closing conversation. Additionally, six communicative functions—referential, emotive, conative, phatic, metalinguistic, and poetic—were identified. These results highlight the structured nature of conversation in media interviews and the role of language functions in shaping interaction, particularly in cross-cultural and multilingual settings. By analyzing this interaction, the study contributes to the broader field of discourse analysis, particularly in media and intercultural communication.